Peran Saung Angklung Udjo Sebagai Sarana Literasi Budaya Di Jawa Barat - Salsabila Ayu Oktaviani; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
As one of the regions with extraordinary cultural wealth, West Java has a variety of arts and cultures that have been passed down from generation to generation. Saung Angklung Udjo is present as one of the realizations of the commitment to preserve and develop traditional arts. In its role, Saung Angklung Udjo not only functions as an art performance venue but also as a cultural literacy tool that plays an important role in maintaining and developing cultural wealth in West Java. Through the combination of quantitative and qualitative methods (mixed methods), this research will try to explain that Saung Angklung Udjo is a cultural literacy tool that plays an important role in West Java. The results showed that based on the questionnaire results, 95.8% of Indonesians agreed with the statements contained in the questionnaire, which means that Saung Angklung Udjo has a very crucial role as a means of cultural literacy in West Java.